Level of Knowledge of Bedside Nursing Staff Regarding Phlebitis of a Tertiary Care Hospital, Karachi: Knowledge of Nursing Staff Regarding Phlebitis - Shaikh, Muhammad Hasnain; Ali, Rizwan; Ahmad, Tufail; Manan, Ahsan; Khan, Ismail; Khan, Muhammad Jehangeer; Bibi, Afsha (Pakistan Journal of Health Sciences, 2023)
Phlebitis is the inflammation of the vein’s inner layer, venous tunica intima called phlebitis. The complications that commonly occur due to phlebitis are erythema, pain, swelling, and palpable thrombosis of the cannulated vein. Objective: To identify the current knowledge of bedside nursing staff regarding phlebitis. Methods: A cross-sectional study was carried out to find knowledge regarding phlebitis among nurses through self-administered questionnaires with 100 bedside nurses working in different wards of a Private Tertiary Hospital in Karachi, Pakistan, by a convenient sampling technique. Data were collected and analyzed by the SPSS software version-22. Results: The result of this study showed that among 100 participants, 50% participants have inadequate knowledge regarding phlebitis, 44% had average, and 6% had good knowledge regarding phlebitis. Conclusions: This study concluded that bedside staff nurses have insufficient knowledge regarding phlebitis. This poor knowledge can reduce the effectiveness of nursing care provided to the patient. Therefore, educational sessions and interventional study needed to enhance their knowledge regarding phlebitis.